Single amino acid loss in the dystrophin protein associated with a mild clinical phenotype. Issue 1 (28th October 2016) - Pons, Roser; Kekou, Kyriaki; Gkika, Artemis; Papadimas, George; Vogiatzakis, Nikolaos; Svingou, Maria; Papadopooulos, Constantinos; Nikas, Ioanis; Dinopoulos, Argirios; Youroukos, Sotiris; Kanavakis, Emmanouel
ABSTRACT: Introduction: The dystrophinopathies include a spectrum of muscle diseases caused by mutations in the dystrophin ( DMD ) gene. The clinical phenotype ranges from severe Duchenne muscular dystrophy to a mild phenotype with elevated creatine kinase (CK). Methods: Clinical and molecular assessment of 7 patients carrying a single amino acid loss in the dystrophin protein (p.His1690del) caused by a c.5068_5070delCAC tri‐nucleotide deletion in exon 36 of the DMD gene. Results: All patients were asymptomatic or oligosymptomatic and had elevated CK levels. Febrile illness, but not exercise, induced muscle symptoms in some patients. None had evidence of cardiomyopathy. Analysis of the short tandem repeat (STR)45 locus and sequencing of exon 36 of the DMD gene indicates that c.5068_5070delCAC is a founder mutation. Conclusions: The c.5068_5070delCAC locus in the DMD gene is associated with a very mild phenotype. Further study is needed to evaluate disease progression in these patients. Muscle Nerve 55 : 46–50, 2017